PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT SINAR12 BUKIT BARISAN GUNUNG SINDUR KABUPATEN BOGOR - Submission JORAPI (Journal of Research and Publication Innovation, 2025)
The purpose of this study was to determine the effect of work motivation and work environment on employee performance at PT Sinar12 Bukit Barisan Gunung Sindur, Bogor Regency. The method used is quantitative. The sampling technique used saturated sampling, and obtained a sample of 50 respondents. Data analysis using validity test, reliability test, classical assumption test, regression analysis, determination coefficient, and hypothesis testing. The results of this study are Work Motivation (X1) has a positive and significant effect on Employee Performance (Y) with a coefficient of determination of 53.5% and hypothesis testing obtained tcount> ttable (1.824> 1.677). Work Environment (X2) has a positive and significant effect on Employee Performance (Y) with a coefficient of determination of 40.1% and hypothesis testing obtained t value> t table or (5.673> 1.677). Work Motivation (X1) and Work Environment (X2) have a positive and significant effect simultaneously on Employee Performance (Y) with a coefficient of determination of 0.620 or 6.20% and hypothesis testing obtained F count 38.307> Ftable 3.20.